Efficiency And Productivity Of The Malaysian Food Manufacturing Industry, 1983-2000 - Radam, Alias (2007)
Food manufacturing industry has been the backbone of Malaysia’s economic stability and growth for decades. The food-manufacturing sector experiences a rather volatile trend during 1993-2000. Due to emphasis given by the government, the manufacturing sector grew by 9.17 percent per annum in 1993 as compared to the previous year, where the sector contributed 45.8 percent to overall increase in GDP. The rate of annual change increment declined from 7.8 percent in 1994 to 6.0 percent in 1995, and this trend continued till 2000. The annual increment dropped by –2.5 percent in 1998, mainly due to the lack of financial support and capital constraints as Malaysia experienced financial crisis during this period. Evidence such as the value of output, exports, employment generations and value added revealed significant disparity. This disparity begs the question as to the sustainability the food manufacturing sector under the rapid growth of other sectors. The relevant indicators have include’s efficiency and productivity of the sector which provide as the benchmark for performance analysis. This study aims to examine the performance of the Malaysian Food Manufacturing Industries in terms of productivity and efficiency during the period 1983 – 2000. The non-parametric Data Envelopment Analysis (DEA), approach are utilized to compute the Malmquist Total Factor Productivity (TFP) indices. The empirical results indicate that only 26.7 percent of the Malaysian food manufacturing industries are closed to the frontier. The average of the technical efficiency of food manufacturing industry increased from 86.5 percent in 1983 to 92.1 percent in 2000. This increase could be due to a gradual narrowing of the gap between the “normal” and “best” practice industries. The average of the scale efficiency of food manufacturing industry increased from 91.8 percent in 1983 to 94.1 percent in 2000 while the average of the pure efficiency of food manufacturing industry increased from 93.9 percent in 1983 to 94.1 percent in the same period. The findings also indicate that between 1983-2000 the annual rate of TFP growth varied. TFP increased by 2.1 percent in 1985, 0.2 percent (1989), 4.2 percent (1990), 4.0 percent (1992), 1.2 percent (1993), 0.1 percent (1997) and 1.7 percent(1998). Overall TFP annual growth rate decreased an average rate of 0.02 percent per annum over the entire 1984-2000 period. Results show that the efficiency change and technical change seem to move in opposite direction. The average technical change (TECHCH) declined over the period under study (-0.6 percent per year) and its contribution to TFP growth is largely due to the increase in the efficiency change (0.4 percent per year). The food manufacturing industries has a strategic role for Malaysia in the context of globalization. The increasing importance of processed food exports when compare with primary commodities confirms this sector as a key component of export growth strategies. At the same time, it was noted that these opportunities are currently heavily concentrated on a limited number of traditional product categories. The empirical estimates of the Malaysian food manufacturing efficiency and productivity performance point to the fact that a greater investment in R&D is needed. To maintain high efficiency, a stable and well-informed environment is called for.